Implementasi Konsep Sistem Mobil pada Perancangan Interior Bengkel Mobil “Kusuma Motor” di Surabaya - Flora Indah Kusuma; Ronald Hasudungan Irianto Sitinjak; Linggajaya Suryanata (Intra, 2018)
The number of cars is currently growing rapidly in Indonesia, especially in big cities like Surabaya. Along with the increasing number of cars, the number of car repair services are also increasing. Considering that car owners want their cars to always look excellent. One of the supporting factors to add more value to the car repair service is by providing nice interior design that will comfort the visitors. From the observation, there is still no public car repair service with the same quality and facilities as authorized services.                The Interior Design of "Kusuma Motor" car repair service in Surabaya was done with several stages, in order for the design process to be more structured. Stages done in the design was based on the design thinking method, which are: discover, empathize, define, ideate, prototype, test.                The design concept of "Kusuma Motor" car repair service is inspired from the car system. The use of the car system concept is because the car has an important role and relation in a car repair service. From the Interior Design of "Kusuma Motor" car repair service, it is expected to provide good car service and to provide an interior design with supporting elements to make the visitors feel comfortable.                In order for “Kusuma Motor” which is a general car repair service to be able to compete with authorized workshops, it is provided with facilities and innovations to support the activities and needs of users in the car repair service in order to become more maximized and to make them feel comfortable. The design is embodied by the space specifications based on function and activities, entertainment facilities, service facilities, etc.